Abscisic Acid-Induced Reactive Oxygen Species Are Modulated by Flavonols to Control Stomata Aperture . Issue 4 (19th October 2017) - Watkins, Justin M.; Chapman, Jordan M.; Muday, Gloria K.
Abstract : Ethylene-regulated synthesis of flavonol antioxidants modulates ABA-induced guard cell closure, light-induced guard cell opening, and leaf transpiration. Abstract: Abscisic acid (ABA) increases reactive oxygen species (ROS) in guard cells to close Arabidopsis ( Arabidopsis thaliana ) stomata. In tomato ( Solanum lycopersicum ), we find that ABA-increased ROS is followed by stomatal closure and that both responses are blocked by inhibitors of ROS-producing respiratory burst oxidase enzymes. ABA-induced ROS sensor fluorescence accumulates in the nucleus, chloroplasts, and endomembranes. The accumulation of flavonol antioxidants in guard cells, but not surrounding pavement cells, was visualized by confocal microscopy using a flavonol-specific fluorescent dye. Decreased flavonols in guard cells in the anthocyanin reduced ( are ) mutant and elevated levels in the anthocyanin without ( aw ) mutant were quantified by confocal microscopy and in leaf extracts by mass spectrometry. Consistent with flavonols acting as antioxidants, higher levels of ROS were detected in guard cells of the tomato are mutant and lower levels were detected in aw both at homeostasis and after treatment with ABA. These results demonstrate the inverse relationship between flavonols and ROS. Guard cells of are show greater ABA-induced closure than the wild type, reduced light-dependent guard cell opening, and reduced water loss, with aw having opposite responses. Ethylene treatment of wild-type tomato plants increased flavonol accumulation in guard cells; however, no flavonol increases were observed in Neverripe ( Nr ), an ethylene receptor mutant. Consistent with lower levels of ROS due to elevated flavonols, ethylene treatments decreased ABA-induced stomatal closure in the wild type, but not Nr, with ethylene responses attenuated in the are mutant. Together, these results are consistent with flavonols dampening the ABA-dependent ROS burst that drives stomatal closure and facilitating stomatal opening to modulate leaf gas exchange.